WIND ENERGY POTENTIAL IN TURKEY - KULUNK, H (ELSEVIER SCI LTD, 1993)
Lewis's methods are employed to evaluate the wind energy potentials of four selected locations, which have experienced relatively high wind velocities. In addition to Lewis's methods, the relations connecting the instantaneous and average wind powers, total and maximum wind energies for a given period of time are derived Characteristics of wind energy, including rotor radius and tower height, are estimated using analytical and graphical approaches. It is concluded that Canakkale with 73.76 W/m2 mean yearly wind power is the most suitable and Florya with a relatively low value Of 26.07 W/m2 is the least suitable for wind energy systems.
Keywords: Energy & Fuels; Engineering